A very rare case report of long-term survival: A patient operated on in 1994 of glioblastoma multiforme and currently in perfect health. (2017) - Caruso, Riccardo; Pesce, Alessandro; Wierzbicki, Venceslao
Highlights: Glioblastoma is the most common and most aggressive type of brain tumors. Prognosis is poor: death occurs within 12–18 months from diagnosis. There is however a small percentage of Patients affected by glioblastoma who survive 3 years or longer. There are some exceptional cases when people have survived decades after surgical removal of a glioblastoma without any recurrence. We report a case of a 44 year-old man operated for a glioblastoma. 22 years after surgery the patient has no recurrence of the tumor. Long-survival depends on young age, complete surgical excision, good Karnofsky index score, radiotherapy and molecular make-up of glioma. Abstract: Introduction: Glioblastoma multiforme is the most aggressive type of primary brain tumors, but there is a small percentage of patients who have a long-term survival and some exceptional cases who survive decades after surgical removal of tumor. Presentation of case: In 1994, a 44 year-old man, suffering from intense headache and loss of strength of the left arm, was operated for a glioblastoma multiforme in the posterior part of the right frontal lobe. After the operation the patient underwent whole-brain radiotherapy and chemotherapy. 22 years after surgery the patient has no recurrence of the tumor. Discussion: A very small percentage of glioblastoma cases showed >3 years survival. There have been exceptional cases of long-survival spanning 10 years or more, without tumor recurrence, so as to deem those affected 'cured'. The long-survival for glioblastoma multiforme is linked to young age, to aggressive and complete surgical excision, a good Karnofsky index score before surgery, the application of radiotherapy after surgery and to the molecular make-up of a specific glioma. Conclusion: The fact that there are extremely rare cases of long-term survival and even zero recurrence of the glioblastoma should serve as a stimulus to continue the research effort and not give up the fight against this tumor on a day-to-day basis.